Психологічні аспекти управління в IT-сфері з урахуванням гендерної компоненти - Тимошенко, Д. О. (ХНУРЕ, 2020)
In the article stresses the importance of human resource management in IT sphere, because human resources there are a basic capital. Analyzed the prospects of these professions in the Ukraine. Attention is drawn to the importance of encouraging employees, adjusting management after the current situation in IT-companies. Іn addition, the problem of gender discrimination in the IT sector and ways to solve it are considered.
Keywords: філософія; психологічні аспекти управління в IT-сфері